(untitled) (Italian Journal of Public Health, 2007)
The “Quit and Win” Campaign is a health promotion campaign that aims to encourage smoking cessation. It is in its fourth edition in Italy and in its sixth edition in Finland. In Italy, it originally started in one region (Veneto, the Italian Coordinating Centre) and has spread to incorporate 11 regions in its latest edition. The aim of this study is to assess the effectiveness, results and trends within the various editions of the campaign. This initiative has been carried out thanks to the collaboration and partnership that exists among the participating regions and the different community services. The involvement of local press and the media have also been utilized to promote the initiative. In addition to this, substantial efforts were made to inform general practitioners, chemists and other health care personnel of the scheme in order that they would promote it by disseminating brochures. Efforts were also made in order to secure sponsorship for the programme. The results from all of the Italian editions have shown an increase in the number of participants, from 5,938 participants in 2000 to 8,185 in 2004 (latest edition). This one ahowed, in 2004, a participation of 4,812 males (M) and 3,373 females (F), a rate of 58.7% and 41.2% respectively; with the largest amount of participants falling into the age class of 25-34 years, accounting for 35.5% M and 32.6% F. 43.4% M and 40.6% F had been smoking for 20 years or more. Strong smokers (> 40 cigarettes/day) accounted for 9.5% of M and 3.1% F. Among all subjects, 47.2% had previously attempted to quit smoking at least once or twice. Among those who had quit smoking for at least four weeks, 39.5% remained non-smokers after one year of follow-up (2004 edition). Most quitters didn’t use any support to replace the effects of the nicotine (79.7%) and half of them didn’t receive any support from those people around them (55.2%). Smokers received information about the campaign in the first edition mainly from health care personnel (46.3%), while in the latest edition the most frequently reported means of obtaining information was via the web-site (31.7%).